Consolidating Digital Partnerships between Academic Libraries in the Middle East and North Africa: A Prospective Study - Abdulla, Mohamed A. (International Journal of Educational Technology and Learning, 2020)
The study aims to discuss the issues of strengthening digital relations between the academic libraries in the MENA and the related issues to the Open access sources, shared databases, sharing intellectual property, and activation of collaboration agendas between MENA academic libraries, by international standards. Also, to review the available partnerships among academic libraries in the Middle East and North Africa, which was the result of the libraries transformation to the digital age. The new role for academic libraries required how joining digital information resources can allow each of the contributing partners to reach new local and worldwide users (Courtney, 2009). There are several forms of academic libraries such as interactive lending, cooperative supply projects, central indexing, union catalogue, reference services, cooperative storage projects, regional cooperation in the field of computers and equipment and exchange of experiences. The current study efforts to highlight review and analyze these partnership issues.